LEGAL LIABILITY FOR FALSE INFORMATION IN NOTARIAL DEEDS - Fail, Aswin Setiadi; Mispansyah (JILPR Journal Indonesia Law and Policy Review, 2025)
This study aims to analyze the forms of notarial liability for deeds containing false information and to determine the legal consequences for deeds that are later proven to be false or not in accordance with applicable provisions. It also examines how the theory of error applies to alleged false information in authentic deeds prepared by notaries. This study uses a normative research method, employing a statutory approach and a case study approach. The legal material collection technique used is a literature study. This legal material analysis technique is based on a normative juridical perspective. The aim is to answer the problems discussed. The first research result: legal liability for parties containing false information in notarial deeds includes criminal liability in the form of imprisonment and civil liability in the form of compensation and administrative sanctions, as stipulated in Law No. 2 of 2014 concerning Notary Positions, resulting in the deed being legally void and becoming a private deed. Second Research Findings: Notaries cannot be held legally accountable without fault, even if there is an alleged violation of the law.